How probing by different parasitoids affects the survival and fecundity of their common host - Cebolla, Ruth; Urbaneja, Alberto; Tena, Alejandro (2018)
Parasitoid acceptance of hosts differs among parasitoid species. Females probe their host with the ovipositor and sometimes they leave the host after probing. Studies of acceptance behaviour in parasitoids have considered the lethal effects of these probes but they have never tackled potential detrimental effects on their host. Here, we compare the effect of probing by two parasitoids, Aphytis melinus DeBach and A. chrysomphali (Mercet) (Hymenoptera: Aphelinidae) that share the same host Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae). Both parasitoids probed a mean of one host in patches of young hosts and these hosts died. When females of both species encountered patches of old scales probed 1.5 hosts but the mortality caused by A. melinus (~55%) was significantly higher than that of A. chrysomphali (~22%). Moreover, contrary to A. chrsysomphali, probing by A. melinus reduced the fecundity of the survival hosts. Overall, our results show that probing should be considered as a biological trait of parasitoids to determine their efficacy as biological control agents and they contribute to understand the higher potential of A. melinus as biological control agent of A. aurantii.